Type locality of the Baya Weaver Ploceus philippinus (Passeriformes, Ploceidae) - Oschadleus, H. Dieter (Zootaxa, 2018)
The Baya Weaver Ploceus philippinus (Linnaeus, 1766) was one of the first weaverbirds to be described, and although Linnaeus (1766) provided its specific epithet and the type locality of the Philippines, the Baya Weaver does not occur there. Hartert (1902, p. 577) thus restricted the locality to Ceylon (now Sri Lanka), and this locality has been used in all major references since, in spite of Stresemann (1952) showing that the type was most probably collected by Pierre Poivre in India. This paper draws attention to this error so that avian handbooks and taxonomic works may refer to the correct type locality of the Baya Weaver as Puducherry (previously Pondicherry), Puducherry district, India.